Mitochondrial myopathy with respiratory muscle involvement: a case report - J. A. Levy; Ana M. Tsanaclis; P. A. P. Saraiva; Carmen C. Mion; Paulo N. B. Salum (Arquivos de Neuro-Psiquiatria)
A case of a 10-year-old patient with a benign congenital myopathy, suddenly aggravated because of an accentuated deficit in respiratory muscles is reported. The institution of assisted respiration at night allowed the patient to return to her daily activities. Examination of muscular biopsy with ultra-microscope permitted the diagnosis of mitochondrial myopathy.